SEMANTIC AND PRAGMATIC ANALYSIS OF THE SPEECH ACT OF IRONY - Abduqodirova Madina Abduqayum qizi (PEDAGOGS, 2025)
Annotation. This study explores the speech act of irony through both semantic and pragmatic lenses. The semantic analysis focuses on the inherent meaning of ironic expressions, examining how literal and intended meanings diverge. The pragmatic analysis investigates the contextual factors that influence the interpretation of irony, including speaker intention, listener inference, and social context. By combining these perspectives, the research aims to provide a comprehensive understanding of how irony functions as a communicative tool in language. The findings contribute to the fields of linguistics, discourse analysis, and communication studies by clarifying the complex interplay between meaning and use in ironic speech